2016
DOI: 10.1016/j.ijid.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Age and Ebola viral load correlate with mortality and survival time in 288 Ebola virus disease patients

Abstract: Patients with a high viral load, of older age, and with diarrhea had a higher mortality and shorter survival time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 13 publications
8
48
0
1
Order By: Relevance
“…Clinical and laboratory factors at presentation that were associated with a fatal outcome included fever, weakness, dizziness, diarrhea, and elevated levels of blood urea nitrogen, aspartate aminotransferase, and creatinine. Age of >45 years and a plasma EBOV load of >10 8 genomes/mL were also associated with fatal outcomes, findings that were subsequently confirmed in other cohorts [31][32][33]. Our clinical study showed that the West African variant of EBOV causes predominately a gastrointestinal illness and focused attention on this aspect for control of disease spread, rather than on bleeding manifestations that predominated in prior outbreaks.…”
Section: Contributions Of Kgh To the Scientific Understanding Of The supporting
confidence: 73%
“…Clinical and laboratory factors at presentation that were associated with a fatal outcome included fever, weakness, dizziness, diarrhea, and elevated levels of blood urea nitrogen, aspartate aminotransferase, and creatinine. Age of >45 years and a plasma EBOV load of >10 8 genomes/mL were also associated with fatal outcomes, findings that were subsequently confirmed in other cohorts [31][32][33]. Our clinical study showed that the West African variant of EBOV causes predominately a gastrointestinal illness and focused attention on this aspect for control of disease spread, rather than on bleeding manifestations that predominated in prior outbreaks.…”
Section: Contributions Of Kgh To the Scientific Understanding Of The supporting
confidence: 73%
“…Patients with EVD have viral loads, peaking above 10 5 copies/mL at the time of presentation [26]. Three studies in Sierra Leone reported a mean EBOV load at admission of 10 6 copies/mL (for 606 patients), 4.89 log copies/mL (for 632 patients), and 6.68 log copies/mL (for 288 patients) [27,28,29]. During the SUDV outbreak in Uganda during 2001, the average peak viremia level in cases with a fatal outcome was 3.4 × 10 9 RNA copies/mL, while in nonfatal cases it was 4.3 × 10 7 RNA copies/mL [26].…”
Section: Discussionmentioning
confidence: 99%
“…7 RNA copies/ml blood at the time of diagnosis (typically seen as C T values of Ͻ25) (4,12,(33)(34)(35)(36). Recent evidence from a longitudinal study of four EVD survivors suggests that C T values greater than ϳ35 in the setting of convalescence are not associated with infectious virus (37); however, a C T value of Յ40 is typically used as the cutoff to designate a positive sample (37).…”
Section: Real-time Rt-pcrmentioning
confidence: 99%